2021
DOI: 10.1002/cam4.4037
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxicity screening of long‐term, breast cancer survivors—The CAROLE (Cardiac‐Related Oncologic Late Effects) Study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…199 The results convincingly demonstrate that a new cancer diagnosis correlated with both CVD morbidity and mortality risk even after adjustment for baseline cardiovascular risk. Furthermore, this CVD risk for several measured outcomes was consistently demonstrated out to 10 years similar to previous evidence from both large observational population studies 198 and smaller targeted studies such as CAROLE (Cardiac-Related Oncologic Late Effects) 200 further strengthening the concept of persistent cancer and cancer therapy-related CVD risk. In keeping with these findings, previously reported evidence from the breast cancer SEER dataset has suggested that cancer may be an risk factor for CVD independent of cancer treatments, such as chemotherapy or radiation therapy.…”
Section: Long-term Outcomes Of Cancer Therapy-related Hypertensionsupporting
confidence: 81%
“…199 The results convincingly demonstrate that a new cancer diagnosis correlated with both CVD morbidity and mortality risk even after adjustment for baseline cardiovascular risk. Furthermore, this CVD risk for several measured outcomes was consistently demonstrated out to 10 years similar to previous evidence from both large observational population studies 198 and smaller targeted studies such as CAROLE (Cardiac-Related Oncologic Late Effects) 200 further strengthening the concept of persistent cancer and cancer therapy-related CVD risk. In keeping with these findings, previously reported evidence from the breast cancer SEER dataset has suggested that cancer may be an risk factor for CVD independent of cancer treatments, such as chemotherapy or radiation therapy.…”
Section: Long-term Outcomes Of Cancer Therapy-related Hypertensionsupporting
confidence: 81%
“…The fourth generation consisted of ML-based CVD risk stratifications using the covariates and gold standard. These images can be collected by using MRI, US, and CT ( 141 ) modalities. CUSIP was collected using automated advanced segmentation algorithms based on scale-space as in generation three.…”
Section: Biological Link Between Atherosclerosis and Cardiovascular D...mentioning
confidence: 99%
“…The CAROLE study evaluated the impact of cardiovascular disease in BC survivors previously treated with anthracycline-taxane, 5-fluorouracil, trastuzumab, pertuzumab and RT; the trial showed a high incidence of cardiovascular disease (77.6% and 51.5% in a preclinical and clinical phase respectively) and these percentages also remained higher in patients treated more than 10 years previously [ 71 ].…”
Section: Side Effects Of Systemic Treatmentsmentioning
confidence: 99%